Disorder or Disadvantage: Investigating the Tension Between Neighborhood Social Structure and the Physical Environment on Local Violence - Barton, Michael S. (Criminal justice review, 2021)
A renewed interest in understanding the relationship of the built environment with neighborhood crime patterns has encouraged researchers to utilize novel methods (e.g., risk terrain modeling) to better examine the influence of environmental risk factors on types of crime. The current study engages with this research by operationalizing neighborhoods using Hipp and Boessen’s egohood strategy and using Drawve’s aggregate neighborhood risk of crime measure to assess the relationship of a neighborhood’s physical environment with its spatial vulnerability of experiencing a homicide. Findings demonstrate that the physical environment was a significant predictor of neighborhood homicide; however, social structural neighborhood characteristics were more important. This suggests crime prevention strategies like crime prevention though environmental design or blight remediation may provide prudent and straightforward methods to inhibit lethal violence in a community in the short run, but that addressing a neighborhood’s social structural characteristics may be more effective at reducing homicides in the long term.